PENGARUH KEPEMILIKAN INSTITUSIONAL DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP TINDAKAN PAJAK AGRESIF - Wening Tiyas Kusumawati, 12.05.52.0188; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the effect of institutional ownership, corporate social responsibility to tax agressive. The sample of this study were companies that listed Corporate Governance Perception Indeks (CGPI). The population in this research is manufacture companies that listed Corporate Governance Perception Indeks (CGPI) in 2011 to 2014. Sampling was done using purposive sampling method. To test and analyze the influence between variables using multiple regression analysis. The results showed that the institutional ownership has significant negative to the tax aggressive, corporate social responsibility has significant positive to the tax aggressive, corporate governance and reurn on assets has no significant positive to the tax aggressive, and corporate social responsibility has significant effect to the tax agressive with corporate governance as moderate variabel.Â  Â Keywords: Institutional Ownership, Corporate Social Responsibility, Corporate Governance, Return On Assets and Tax Agressive